PWE-022 Gut-homing TH17 cells are selectively targeted by vedolizumab and may predict clinical response in IBD. (8th June 2018) - Hermangild Kottoor, Sherine; Scotta, Cristiano; Pavlidis, Polychronis; Alberts, Ellie; Kassam, Zain; Constable, Laura; Metoudi, Michael; Digby-Bell, Jonathan; Ibraheim, Hajir; Warren, Dawn; Samaan, Mark; Irving, Peter; et al.
Abstract : Introduction: Trafficking of inflammatory lymphocytes to the gut plays a central role in IBD pathogenesis. We analysed the profile of circulating gut homing effector memory T cell subsets in IBD patients. We also evaluated the impact of treatment with Vedolizumab, a monoclonal antibody that binds to integrin α4 β7 (β7) and prevents binding to its ligand MAdCAM-1, thereby preventing lymphocyte migration to the gut. Methods: Using multi parametric flow cytometry, we analysed the gut homing (β7+) effector T-cells (CD3 + CD4 + CD45RO + CD45RA - CCR7 - ) including different functional lineages: Th1 (CXCR3 + CCR6 - ); Th2 (CXCR3 - CCR6 - CCR4 + ); Th17 (CXCR3 - CCR6 + ) and Th1/17 (CXCR3 + CCR6 + ) from peripheral blood (PB) of healthy controls (HC, n=42) and IBD (n=34) patients, including a prospective analysis of new starters of vedolizumab. Peripheral blood was taken from patients before their first dose of vedolizumab and at each subsequent infusion. Results: Compared to HC, the proportion of Th1 cells within the gut homing compartment was significantly decreased in PB of IBD patients (median HC 27.3% vs IBD 44%, p<0.0006). In contrast, the proportion of Th17 cells within the gut homing compartment was significantly increased (HC 12% vs IBD 19%, p<0.003). This difference was most striking in ulcerative colitis. There was no significance difference in Th1/17 or Th2 cells in IBD vs HC. In the longitudinal analysis, there was minimal impact on gut homing Th1 cells in vedolizumab treated patients (comparison between baseline and week 8), however, the gut homing Th17 compartment increased over the same time period (from 19.3% at baseline to 29.7% at week 8). The proportion of gut homing Th17 was significantly higher in vedolizumab treated patients at week 8 in comparison to infliximab (n=3) treated IBD patients (37.3% vs 18.3%, p<0.02). There was no change in the proportion of Th1 cells expressing β7 in these groups. Intriguingly, preliminary data indicated that clinical response to vedolizumab (30% fall in HBI or SCCAI at week 8) was associated with a significantly higher median number of Th17 cells expressing β7 compared to non-responders (responders: 46.8% vs non-responders: 29.7%, p<0.04). Conclusions: IBD is characterised by an expansion of circulating gut homing Th17 cells, which is yet further increased following institution of vedolizumab therapy. The magnitude of change could also differentiate between responders and non-responders to treatment, raising the possibility that this test could be used as an early warning biomarker to aid decision making in clinical practice.